Metal-free [2+2+1] cycloaddition polymerization of alkynes, nitriles, and oxygen atoms to functional polyoxazoles. Issue 41 (25th June 2020) - Dong, Lichao; Lan, Tian; Liang, Yin; Guo, Shifeng; Zhang, Hao
Abstract : The metal-free [2+2+1] cycloaddition polymerization of alkynes, nitriles, and O-atoms for the regioselective assembly of highly substituted oxazole compounds has been achieved by the use of iodosobenzene (PhIO) with trifluoromethanesulfonic acid (TfOH). Abstract : The metal-free [2+2+1] cycloaddition polymerization of alkynes, nitriles, and O-atoms for the regioselective assembly of highly substituted oxazole compounds has been achieved by the use of iodosobenzene (PhIO) with trifluoromethanesulfonic acid (TfOH). The present reaction could be applied to a facile synthesis of polyoxazoles. In this work, the cycloaddition polymerization of 4-cyano-4′-ethynylbiphenyl and PhIO was developed and modified polyoxazole was prepared. All experimental conditions such as polymerization solvent, temperature, catalyst and time were systematically studied. The structure of the obtained polyoxazole was characterized by GPC and NMR, and its thermal properties were studied by TGA. In addition, the good thermal stability of polyoxazoles with unreacted terminal alkynes and cyano groups makes them potentially useful for modifying resins.